Low Triiodothyronine Syndrome in Patients With Radiation Enteritis: Risk Factors and Clinical Outcomes an Observational Study. Issue 6 (February 2016) - Fan, Shengxian; Ni, Xiaodong; Wang, Jian; Zhang, Yongliang; Tao, Shen; Chen, Mimi; Li, Yousheng; Li, Jieshou
Abstract : Abstract: The implications of low triiodothyronine syndrome (LT3S) in patients with radiation enteritis (RE) have not been properly investigated. As such, we conducted this cohort study to investigate the association between LT3S and RE, to explore the etiology of LT3S in RE, to evaluate the clinical features and clinical outcomes of LT3S patients, and to inspect the correlation of clinical variables and LT3S in RE. This prospective study included 39 RE patients. Medical records and various laboratory parameters (including thyroidal, tumorous, nutritional, and radiotherapy variables) were collected in all participants. Our results showed that the incidence of LT3S was 84.6% in patients with RE. Total protein (71.7 ± 5.7 vs 63.2 ± 9.6 g/L, P  = 0.04) and albumin (ALB, 46.0 ± 4.6 vs 38.7 ± 5.3 g/L, P  = 0.01) were significantly lower in LT3S group compared with those in euthyroid group. Standard thyroid-stimulating hormone index (−0.89 ± 2.11 vs −2.39 ± 1.33, P  = 0.03) and sum activity of deiodinases (19.74 ± 4.19 vs 12.55 ± 4.32 nmol/L, P  = 0.01) were significantly lower in LT3S group. Patients with LT3S suffered longer duration of hospitalization (48.25 ± 23.29 days in LT3S vs 26.75 ± 10.56 days in euthyroid, P  = 0.036). Low serum ALB (β = 0.694, 95% CI = 0.007–0.190, P  = 0.037) was the only significant predictor of LT3S. LT3S was common in RE patients. A hypodeiodination condition and a potential pituitary-thyrotroph dysfunction might play a role in the pathophysiology of LT3S in RE. Worse nutritional status and clinical outcomes were confirmed in RE patients with LT3S. Furthermore, total protein and ALB were observed as protective and differentiating parameters of LT3S in RE. In summary, this was the 1st investigation to evaluate the clinical correlation between RE and LT3S, investigate the prevalence of LT3S in RE, and explore the pathogenesis of LT3S, despite the limitation of a relatively small sample size. These results will hopefully encourage future research to place greater emphasis on early identification of LT3S in RE patients.